2022
DOI: 10.3389/fpubh.2022.883204
|View full text |Cite
|
Sign up to set email alerts
|

Effective Teaching Behaviors of Clinical Nursing Teachers: A Qualitative Meta-Synthesis

Abstract: ObjectivesTo identify, appraise, and synthesize the available evidence exploring the effective teaching behaviors of clinical nursing teachers.DesignThe Joanna Briggs Institute (JBI) guidelines were followed, and a meta-synthesis was conducted.Review MethodsFollowing databases were searched for relevant qualitative studies published in English and reporting primary data analysis, including experiences and perceptions of nursing students: PubMed, EBSCOhost, OVID, etc. Qualitative Assessment and Review Instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…However, some studies also indicated negative experiences ( 29 , 31 ). On the one hand, the clinical instructors should establish their roles, not only to become clinical nurse role models but also to become knowledgeable, trustworthy teachers ( 46 ). On the other hand, hospital management departments should provide opportunities for clinical instructors to complete higher-level academic education and take psychology and pedagogy courses, which can facilitate them master flexible teaching ways and deepen their understanding of intensive care unit professional development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies also indicated negative experiences ( 29 , 31 ). On the one hand, the clinical instructors should establish their roles, not only to become clinical nurse role models but also to become knowledgeable, trustworthy teachers ( 46 ). On the other hand, hospital management departments should provide opportunities for clinical instructors to complete higher-level academic education and take psychology and pedagogy courses, which can facilitate them master flexible teaching ways and deepen their understanding of intensive care unit professional development.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, critical care nurses assumed tremendous caring responsibility for critically ill patients at the same time. This required hospital management departments to formulate a standardized assessment mechanism for clinical instructors and to rationalize the allocation of ICU nursing human resources to prevent clinical instructors from burnout and exhaustion ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Energy management involves regulating and optimizing personal energy levels to enhance performance, while thriving involves flourishing in multiple domains of life, including work. Different energy management strategies, including emotional, mental, and physical, are positively associated with work engagement (Zhang et al, 2022), which is related to thriving (Saks, 2006). Studies have also indicated that energy management enhances positive affect, a source for thriving at work (Spreitzer et al, 2005).…”
Section: Thrivingmentioning
confidence: 99%
“…Proper exercise and movement (cardiovascular and strength training), nutrition (a balanced combination of carbohydrates, fats, and proteins), and sleep (seven to eight hours per 10.3389/fpsyg.2023.1239587 Frontiers in Psychology 04 frontiersin.org night) increase positive moods during the workday (Spreitzer and Grant, 2012). Emotional energy management has been found to be effective in activating recovery processes (Zhang et al, 2022). Individuals adopt strategies like energy audits to sustain their energy levels (Spreitzer and Grant, 2012).…”
Section: Thrivingmentioning
confidence: 99%
“…Consequently, they are perceived as the fundamental link between learners, healthcare professionals, and patients. To optimally perform their responsibilities, these faculty members must possess certain essential professional traits such as comprehensive professional knowledge, proficiency in clinical procedures, excellent communication skills, and the ability to be exemplary role models [4] . Faculty members must communicate well, anticipate and respond to student feedback and needs, and demonstrate proficiency in both in-person and online pedagogical methodologies [5] .…”
Section: Introductionmentioning
confidence: 99%